10.10: Influence of beam‐end buckling on adjacent beam‐column connections in fire. (13th September 2017) - Quan, Guan; Huang, Shan‐Shan; Burgess, Ian
ABSTRACT: An analytical model to simulate the beam‐end buckling phenomenon, which occurs particularly in the fire context, has been developed. In this research, a component‐based beam‐end buckling element has for the first time been created for beams of Classes 1 and 2. The component‐based buckling element is composed of nonlinear springs, which can deal with loading‐unloading‐reloading paths. A significant challenge is to enable the flange‐buckling component to deal with a descending post‐buckling path simultaneously with deformation‐reversal, because more than one solution can be found at a single force level in the solution process. The buckling element has been implemented in the structural fire engineering software Vulcan, so that it can be used adjacent to existing connection elements in frame modelling. The effects of the buckling element have been investigated in frame analysis using Vulcan . It has been shown that, in most cases, the stresses within the connection's bolt rows tend to decrease when the buckling element is taken into consideration. By ignoring the buckling element near to the beam‐to‐column connections in structural fire analysis, the results tend to be on the safe side regarding the connection forces.